Determinants of Retirement Financial Planning, Asset Ownership, and Economic Pressure on the Wellbeing of Post-Retirement Households, Moderated by Financial Literacy (survey of post-retirement households in Surakarta) - Susanti, Rina; Indriastuti, D Ririn; Wulandari, Rina (International Journal of Economics, Business and Innovation Research, 2025)
Post-Post-retirement family welfare is something that everyone wants after the completion of their retirement period. This is because a person's income at this time is different from their productive age when they were still working. To be able to realize retirement welfare, long preparation is needed, since a person is still at a productive working age. The driving factors include financial planning in old age, asset ownership, and economic pressure. This will have a better impact if it is reinforced with good financial management knowledge by a person in managing their finances. In this study, the researcher used three independent variables, one dependent variable, and one moderating variable. The data obtained from the distribution of questionnaires were tabulated and then tested using SPSS. The purpose of this study was to determine the determination of financial planning in old age, asset ownership, and economic pressure on post-retirement family welfare moderated by financial literacy